Case report: Disseminated Scedosporium apiospermum infection with invasive right atrial mass in a heart transplant patient - Bourlond, Baudouin; Cipriano, Ana; Regamey, Julien; Papadimitriou-Olivgeris, Matthaios; Kamani, Christel; Seidel, Danila; Lamoth, Frederic; Muller, Olivier; Yerly, Patrick (Frontiers in Cardiovascular Medicine, 2022)
Scedosporium apiospermum associated endocarditis is extremely rare. We report a case of a disseminated S. apiospermum infection with an invasive right atrial mass in a 52-year-old male, 11 months after heart transplantation, referred to our institution for an endogenous endophthalmitis with a one-month history of diffuse myalgias and fatigue. The patient had been supported two times with extracorporeal membrane oxygenation (ECMO) during the first three postoperative months. The echocardiography on admission revealed a mass in the right atrium attached to a thickened lateral wall. The whole-body [18F]FDG PET/CT revealed systemic dissemination in the lungs, muscles, and subcutaneous tissue. Blood cultures were positive on day three for filamentous fungi later identified as S. apiospermum. The disease was refractory to a 3-week dual antifungal therapy with voriconazole and anidulafungin in addition to reduced immunosuppression, and palliative care was implemented.